Synthesis and Characterization of Mechanical Properties of AA8014 + Si3N4/ ZrO2 Hybrid Composites by Stir Casting Process - C. Ramesh Kannan; R. Venkatesh; M. Vivekanandan; J. Phani Krishna; S. Manivannan; S. Rajkumar; V. Vijayan (Advances in Materials Science and Engineering)
Lightweight materials are extremely needed for the manufacturing of industrial parts and are used in aerospace, automobile body shops, biomedical instruments, etc. Aluminium alloy is one of the light-weight materials, and it fulfills the industrial demands based on their natural strength/stiffness, enhanced temperature permanence, superior wear, and corrosion resistance. This experimental work considered aluminium alloy (AA8014) with reinforced particles of silicon nitride (Si3N4) and zirconium dioxide (ZrO2) for preparing aluminium hybrid composites. Hybrid composites are prepared by a stir casting process involving different process parameters. L27 orthogonal array is used for optimizing the stir casting parameters with the assistance of the statistical Taguchi approach. Stir casting parameters are the percentage of reinforcement (4%, 6%, and 8%), stir speed (400 rpm, 500 rpm, and 600 rpm), stir time (20 min, 25 min, and 30 min), and molten temperature (700 oC, 800 oC, and 900 oC). Mechanical performance such as wear and microhardness of the hybrid composites is evaluated. Minimum wear and higher microhardness are encountered at a percentage of reinforcement = 6%, stir speed = 400 rpm, stir time = 30 min, and molten temperature = 900°C. In wear analysis, the percentage of reinforcement highly influences the wear properties (7.06% contribution). In microhardness analysis, molten temperature parameter is the extreme influencer (11.15% contribution).